Giant sublacustrine landslide in the Cretaceous Songliao Basin, NE China. (9th April 2019) - Pan, Shuxin; Liu, Caiyan; Li, Xiangbo; Liang, Sujuan; Chen, Qilin; Zhang, Wenting; Zhang, Shuncun
Abstract: Mass failure deposits in lacustrine settings are some of the most understudied facies associations in the ancient or modern rock record. We integrated seismic data and well logs to investigate the external morphology, internal architecture and deformation and reservoir distribution of the sublacustrine landslides in the Cretaceous Nengjiang Formation of the Songliao Basin (SLB). A large‐scale sublacustrine landslide, named the Qi‐Jia sublacustrine landslide (QJSL), has been identified in the Nengjiang Formation of the SLB. The QJSL is currently the largest known sublacustrine landslide in the world. This landslide covers an area that exceeds 300 km 2, with an estimated volume of 30 km 3 . Seismic imaging and mapping reveal that the QJSL can be recognized by several distinguishing seismic characteristics: discontinuous and internal chaotic seismic facies, compressional structures in the downslope region, irregular top and basal surfaces and erosional grooves in basal shear surfaces. The QJSL is 20–200 m thick, and is composed of a succession of fine‐grained deposits. Sandy layers are present but sparse and thinner than 16 m, and form reservoirs of the petroleum discoveries in this area. Our analyses show that the mechanism that triggered the collapse of the QJSL is attributed to rapid deposition and deltaic progradation. This study demonstrates that sand‐rich sublacustrine landslides formed at delta front slope can serve as conventional reservoirs in the lake centre, and provide a new target for subaqueous hydrocarbon exploration and development.